Pemetaan Terumbu Karang Berbasis Citra Unmanned Aerial Vehicle (UAV) Dan Satelit Sentinel-2A Dengan Metode Object Based Image Analysis (OBIA) Di Perairan Pulau Menjangan Bali - Ahmad, Ramadhani; Putra, I Dewa Nyoman Nurweda; Darmendra, I Putu Yogi (Journal of Marine Research and Technology; Vol 7 No 1 (2024): FEBRUARI 2024, 2024)
There is still little research on mapping benthic habitats on Menjangan Island, so the availability of spatial data in this area is still limited. This research aimed to map coral reefs using UAV imagery and Sentinel-2A imagery with the object-based/OBIA classification method and calculate the level of accuracy of classification results in the waters of Menjangan Island. This research was conducted in 4 water areas, especially waters where diving and snorkeling activities often occur. This research used Sentinel-2A satellite data acquired on March 17, 2022, and UAV data acquired on March 30, 2022. Area 1 live coral (KH) with an area of 0.76 Ha for UAV imagery, live coral (KH) on Sentinel imagery -2A, namely 0.64 Ha. Region 2, the area of live coral (KH) in the UAV image is 0.67 Ha, and live coral (KH) in the Sentinel-2A image is 0.49 Ha. Region 3, the area of live coral (KH) in the UAV image is 0.77 Ha; in the Sentinel-2A image, it is 0.60 Ha. The 4 live coral (KH) areas in the UAV image have an area of 0.83 Ha, and the live coral (KH) in the Sentinel-2A image covers an area of 0.62091 Ha. UAV imagery can produce an overall accuracy in each region of 97.96% in Region 1. 98.21% in Region 2, 98.84% in Region 3, and 96.77% in Region 4. The overall accuracy level of Sentinel-2A imagery is 85.71% in Region 1, 83.93% in Region 2, 86.05% in Region 3, and 83.87% in Region 4.